2006
DOI: 10.2175/106143006x95465
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Constructed Wetland‐Pond System for Treatment and Reuse of Wastewater from Campus Buildings

Abstract: A constructed wetland-pond system consisting of two freewater-surface-flow (FWS) wetland cells, a scenic pond, and a slag filter in series was used for reclamation of septic tank effluent from a campus building. The results show that FWS wetlands effectively removed major pollutants under a hydraulic loading rate between 2.1 and 4.2 cm/d, with average efficiencies ranging from 74 to 78% for total suspended solids, 73 to 88% for 5-day biochemical oxygen demand, 42 to 49% for total nitrogen, 34 to 70% for total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Liu et al (2013) reported TN removal rates of 0.69–1.2 g/m 2 ·d for nonaerated VF CWs . Maltais-Landry et al (2009) and Zhang et al (2010) achieved averaged TN removal rates in aerated CWs at 0.8 and 5.0 g/m 2 ·d, respectively. , Other similar studies reported typical TN removal rates ranging from 0.9 to 4.6 g/m 2 ·d. ,, Thus, our single-stage TF CWs exhibited promising performance and operational flexibility for nitrogen removal (both NH 4 + and NO 3 – ), allowing TF CWs to complement and even replace hybrid CW systems in field applications, while providing more efficient space utilization and lower capital costs.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Liu et al (2013) reported TN removal rates of 0.69–1.2 g/m 2 ·d for nonaerated VF CWs . Maltais-Landry et al (2009) and Zhang et al (2010) achieved averaged TN removal rates in aerated CWs at 0.8 and 5.0 g/m 2 ·d, respectively. , Other similar studies reported typical TN removal rates ranging from 0.9 to 4.6 g/m 2 ·d. ,, Thus, our single-stage TF CWs exhibited promising performance and operational flexibility for nitrogen removal (both NH 4 + and NO 3 – ), allowing TF CWs to complement and even replace hybrid CW systems in field applications, while providing more efficient space utilization and lower capital costs.…”
Section: Resultssupporting
confidence: 56%
“…36,37 Other similar studies reported typical TN removal rates ranging from 0.9 to 4.6 g/m 2 •d. 28,38,39 Thus, our single-stage TF CWs exhibited promising performance and operational flexibility for nitrogen removal ( + and TN by 19 ± 5.4% and 35 ± 5.1%, respectively. The negligible nitrification observed in Figure 2a suggests that the biological NH 4 + transformation contributes little to NH 4 + removal due to the negative impact of the low influent temperature (15.1−16.2 °C) on nitrifying bacteria, which are slow-growing chemoautotrophic organisms with optimal growing and functioning conditions above 30 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…In contrast, very little research effort has been devoted to investigating the removal of contaminants from wastewater with CPs. Ou et al (2006) investigated the performance of a CW-CP system for treatment and reuse of wastewater from campus buildings. These authors found that the percent removals of total suspended solids, total nitrogen, and total phosphorus are, respectively, 24, 87, and 62 % with the pond.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study on pollutant emission laws of campus sewage coming from different source. According to the prior pollution factors to design different treatment process, and choose appropriate sewage treatment technology to reduce the pollution load and the cost of follow-up treatment [5][6][7]. Due to the difference between geographical areas and climate, the student's food habit, bathing and activities at different frequencies are different in domestic universities.…”
Section: Introductionmentioning
confidence: 99%